Optimizing ZIS Awareness through Dakwah Communication Strategy: A Case Study of BAZNAS Makassar City - Hasdar, Hasdar; Shamad, M. Ishaq; Syamsuriah, Syamsuriah (Lembaga Sembilan Tiga Community, 2025)
Zakat, Infaq, Alms (ZIS), and Other Religious Social Funds (DSKL) are pivotal for equitable welfare distribution and poverty alleviation in Indonesia. However, public compliance remains suboptimal due to uneven awareness. This study explores the da’wah communication strategies employed by BAZNAS Makassar City to enhance public awareness and participation in ZIS and DSKL payments while identifying implementation challenges. Utilizing a qualitative descriptive approach, data were gathered through in-depth interviews, field observations, and documentation involving key informants from BAZNAS Makassar City. The findings reveal that BAZNAS Makassar adopts a multi-channel communication strategy, integrating direct outreach via Zakat Collection Units (UPZ), digital transformation through websites and social media, and strategic collaboration with the Makassar City Government via the Automatic Deduction (PO) System for civil servants' salaries. These strategies are executed through segmented, persuasive, and educational approaches tailored to diverse audience demographics. Despite these efforts, obstacles such as inconsistent participation from volunteer preachers, internal resistance to salary deductions, and low zakat literacy persist. This study suggests that strengthening preacher capacity and diversifying digital communication media are essential for building institutional trust. These findings provide a strategic framework for zakat institutions to develop more adaptive and sustainable communication models in a contemporary religious context. Keywords: Da’wah Communication, Zakat Management, BAZNAS, Public Awareness, ZIS